2016
DOI: 10.3389/fmicb.2016.01163
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Chemosynthetic Microbial Mats Associated with Intertidal Hydrothermal Sulfur Vents in White Point, San Pedro, CA, USA

Abstract: The shallow-sea hydrothermal vents at White Point (WP) in Palos Verdes on the southern California coast support microbial mats and provide easily accessed settings in which to study chemolithoautotrophic sulfur cycling. Previous studies have cultured sulfur-oxidizing bacteria from the WP mats; however, almost nothing is known about the in situ diversity and activity of the microorganisms in these habitats. We studied the diversity, micron-scale spatial associations and metabolic activity of the mat community v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 119 publications
2
14
0
Order By: Relevance
“…Sequences related to the genus B46 within Gammaproteobacteria with 95% similarity to Methylomolas and Methylococcaceae were also recovered. Similar sequences have been recovered from the Tica vent on the East Pacific Rise deep-sea hydrothermal vent system (GenBank accession number KT257824) (Gulmann et al, 2015) as well as microbial mats at White Point, California (GenBank accession number KX422153) (Miranda et al, 2016) indicating potential occurrence of methylotrophy in addition to chemoautotrophy. Successful isolation of Sedimenticola thiotaurini , another sulfur-oxidizing chemolithotroph belonging to Gammaproteobacteria , further confirmed their dominance in the EF.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Sequences related to the genus B46 within Gammaproteobacteria with 95% similarity to Methylomolas and Methylococcaceae were also recovered. Similar sequences have been recovered from the Tica vent on the East Pacific Rise deep-sea hydrothermal vent system (GenBank accession number KT257824) (Gulmann et al, 2015) as well as microbial mats at White Point, California (GenBank accession number KX422153) (Miranda et al, 2016) indicating potential occurrence of methylotrophy in addition to chemoautotrophy. Successful isolation of Sedimenticola thiotaurini , another sulfur-oxidizing chemolithotroph belonging to Gammaproteobacteria , further confirmed their dominance in the EF.…”
Section: Discussionmentioning
confidence: 59%
“…Previous field observations of the distribution of microorganisms in biofilms from geothermal habitats indicated that Epsilon - and Gammaproteobacteria are spatially segregated, with the former dominating higher sulfide habitats and the latter being more prevalent in lower sulfide, possibly more oxic habitats (Engel et al, 2004; Reigstad et al, 2011; Giovannelli et al, 2013; O’Brien et al, 2015; Miranda et al, 2016). Based on these observations, and on the high concentrations of sulfide measured in the gases at Tor Caldara (Table 1), we had predicted that the EF biofilms would be dominated by sulfide-oxidizing Epsilonproteobacteria .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, in addition to chemosynthetic processes, microbial communities of shallow-water systems may also use light for the production of biomass via photosynthesis, resulting in high biological productivity and likely even more complex microbial communities relative to the deep-sea counterparts (Wang et al, 2015 ). Despite this, little is known about the ecology of microbial communities of shallow-water hydrothermal systems and they remain largely understudied compared to their deep-sea counterparts (Dawson et al, 2016 ; Miranda et al, 2016 ; Gomez-Saez et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%